HUBUNGAN PEMANFAATAN SUMBER BELAJAR DENGAN HASIL PEMBELAJARAN GEOGRAFI SISWA KELAS X SMAN 9 PONTIANAK - Supiani, Eka; Tampubolon, Budiman; Sugiarto, Agus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research is conducted to describes availability and utility of learning resources, to know study result and relation between resources utilization and study result in student of X social class in SMAN 9 Pontianak. This research used descriptive method with formed correlation study. The research populationconsisted of 142 students, from four class with the sample are 58 students. Data in this research is resources utilization and study result student data, there are mean of exam daily value in even semester in 2017/2018. Data aggregation method that used is direct observation, indirect communication, and study documenter. Tools that used to aggregating data is observation guidelines, inquiry or questionnaire and documentation. Analysis data method that used is with condition analysis and hypothesis. Due to research mean result about utilization of study resources is about 71.62 or 55.95%, and mean study result of student is about 73.83. This result rxycount calculated about 0.73 (X Social 1 and Social 2 Classes) and 0.54 (X Social 3 and Social 4 Classes) with rtable (significant level about 5% and free degree=27) is 0.367 with means are rxycount (0.73)> rtable(0.367) and rxycount (0.54)> rtable(0.367) where due to that result make ha accepted. This mean there are relation between utilization of study resources and study result in geography studies in X class at SMAN 9 Pontianak.Keyword: study resources utilization, geography exam study result